The Thief Lord - Funke, Cornelia, 1958-; Funke, Cornelia, 1958-; Latsch, Oliver (New York : Scholastic, 2002)
Orphaned brothers Prosper and Bo, having run away from their cruel aunt and uncle, decide to hide out in Venice where they fall in with the Thief Lord, a thirteen-year-old boy who leads a crime ring of street children.
Translation of: Herr der Diebe.
"The Chicken House.".
Originally published: Hamburg, Germany : Cecile Dressler, c2000.
"First published in the United Kingdom in 2002 by The Chicken House ... Somerset"--T.p. verso.
Wilson's Junior High School, November 2005.
School Library Journal starred, October 2002.
Keywords: Runaways -- Fiction; Robbers and outlaws -- Fiction; Brothers -- Fiction; Detectives -- Fiction; Runaway children -- Fiction; Brothers -- Fiction; Mystery fiction; Thieves -- Fiction; Runaways -- Fiction; Robbers and outlaws -- Fiction; Brothers -- Fiction; Detectives -- Fiction; Venice (Italy) -- Fiction; Italy -- Fiction; Venice (Italy) -- Fiction; Italy -- Fiction; Venice (Italy) -- Fiction; Italy -- Fiction